Exploratory study on the ascending pain pathway in patients with chronic neck and shoulder pain based on combined brain and spinal cord diffusion tensor imaging - Zhiqiang Qiu; Tianci Liu; Chengxi Zeng; Maojiang Yang; HongYing Yang; Xiaoxue Xu (Frontiers in Neuroscience)
ObjectiveTo explore the changes in the white matter microstructure of the ascending pain conduction pathways in patients with chronic neck and shoulder pain (CNSP) using combined brain and spinal cord diffusion tensor imaging techniques, and to assess its correlation with clinical indicators and cognitive functions.Materials and methodsA 3.0T MRI scanner was used to perform combined brain and spinal cord diffusion tensor imaging scans on 31 CNSP patients and 24 healthy controls (HCs), extracting the spinothalamic tract (STT) and quantitatively analyzing the fractional anisotropy (FA) and mean diffusivity (MD) which reflect the microstructural integrity of nerve fibers. Additionally, these differences were subjected to partial correlation analysis in relation to Visual Analog Scale (VAS) scores, duration of pain, Self-Rating Anxiety Scale (SAS), and Self-Rating Depression Scale (SDS).ResultsCompared to HCs, CNSP patients showed decreased mean FA values and increased mean MD values in bilateral intracranial STT compared to the HC group, but two-sample t-test results indicated no statistically significant differences (p > 0.05). FA values of the left STT (C2 segment, C5 segment) and right STT (C1 segment, C2 segment) were significantly decreased in bilateral cervical STTs of CNSP patients; MD values of the left STT (C1 segment, C2 segment, C5 segment) and right STT (C1 segment, C5 segment) were significantly increased (p < 0.05). Partial correlation analysis results showed that FA values of STT in CNSP patients were negatively correlated with VAS scores, duration of pain, SAS scores, and SDS scores, while MD values were positively correlated with VAS scores and duration of pain (Bonferroni p < 0.05).ConclusionThis research identified that patients with CNSP exhibited reduced mean FA and increased mean MD in the bilateral intracranial STT, although these differences were not statistically significant (p > 0.05). Conversely, significant abnormalities were observed in specific segments of the bilateral cervical STT (p < 0.05), which were also correlated with variations in pain intensity, illness duration, and levels of anxiety and depression. These findings contribute a novel neuroimaging perspective to the evaluation and elucidation of the pathophysiological mechanisms underlying chronic pain in the ascending conduction pathways.